2010
DOI: 10.1002/jmri.22414
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted magnetic resonance imaging of pancreatic adenocarcinomas: Association with histopathology and tumor grade

Abstract: Purpose: To evaluate the utility of diffusion-weighted magnetic resonance imaging (DWI) in pancreatic ductal adenocarcinoma with various grades of differentiation. Materials and Methods:Following Institutional Review Board (IRB) approval, 21 consecutive patients with surgical pathology-proven pancreatic adenocarcinomas were retrospectively evaluated. Histopathologic characteristics and grades of differentiation of adenocarcinomas were analyzed. Twenty-one patients without a known history of pancreatic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
92
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 26 publications
18
92
0
1
Order By: Relevance
“…Details on the most relevant published studies are reported in Table 2. Overall, low-grade PDACs tend to present low ADC values [43][44][45] , but it still not clear which histological feature mainly contributes to diffusion restriction. Wang et al [43] and Muraoka et al [46] reported that tumors with limited glandular formation and dense fibrosis (i.e., paucicellular tumors) had lower ADC values as compared to welldifferentiated lesions characterized by neoplastic tubular structures; moreover, PDACs with dense fibrosis showed significantly lower ADC values than those with loose fibrosis.…”
Section: Pancreatic Tumorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Details on the most relevant published studies are reported in Table 2. Overall, low-grade PDACs tend to present low ADC values [43][44][45] , but it still not clear which histological feature mainly contributes to diffusion restriction. Wang et al [43] and Muraoka et al [46] reported that tumors with limited glandular formation and dense fibrosis (i.e., paucicellular tumors) had lower ADC values as compared to welldifferentiated lesions characterized by neoplastic tubular structures; moreover, PDACs with dense fibrosis showed significantly lower ADC values than those with loose fibrosis.…”
Section: Pancreatic Tumorsmentioning
confidence: 97%
“…Overall, low-grade PDACs tend to present low ADC values [43][44][45] , but it still not clear which histological feature mainly contributes to diffusion restriction. Wang et al [43] and Muraoka et al [46] reported that tumors with limited glandular formation and dense fibrosis (i.e., paucicellular tumors) had lower ADC values as compared to welldifferentiated lesions characterized by neoplastic tubular structures; moreover, PDACs with dense fibrosis showed significantly lower ADC values than those with loose fibrosis. Fibrosis may be therefore the key factor contributing to diffusion restriction in PDACs, but these findings have not been confirmed by other studies: particularly, Klauss et al [47] reported that the difference between the IVIM-derived D value (diffusion) of moderate and severe fibrosis PDACs was significant, but the cellular complexes surrounded by fibrosis formed only on solid areas showing diffusion restriction.…”
Section: Pancreatic Tumorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The technique may be useful in determining pathology in the liver (degree of cirrhosis/fibrosis), kidneys (lesion characterization, renal failure, pyelonephritis), pancreas (pancreatitis and pancreatic cancer), bowel (Crohn's disease), and uterus (endometriosis) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . In a recent meta-analysis, Li et al [19] has shown a potential future role for this type of sequence to assess for cancers within the liver.…”
Section: Introductionmentioning
confidence: 99%